Analysis and modeling of dust accumulation-composed spherical and cubic particles on PV module relative transmittance. (April 2021) - Wu, Ze; Yan, Suying; Ming, Tingzhen; Zhao, Xiaoyan; Zhang, Na
Abstract: PV modules are exposed to outdoor environments where dust accumulation affects optical performance. In this paper, a mathematical model is proposed to predict the impact of dust accumulation based on the shape of dust particles on the relative transmittance of PV. The model considers the light path into the dust particle. The changes of the light path are simulated through Tracepro soft. The variation of the relative transmittance with the dust-deposited density is tested and verified based on an experiment of artificial dust distribution. The results indicated that the dust of cubic particles caused a larger decrease in the relative transmittance compared with the dust of spherical particles. The relative transmittance of the spherical dust decreases from 100% to 77.64%, while that of the cubic dust decreases from 100% to 65.53%, when dust-deposited density is 10 g/m 2 . However, the opposite trend is seen when the light-receiving area is equal to the occlusion area of a dust particle in the simulation. The maximum relative deviation between the mathematical model and the experimental results was only 1%.